Notes on Images of the World and Inscription of War - Arçari, André; Capistrano, Tadeu (Farol, 2024)
This essay brings together written notes that precede frames from Images of the World and Inscription of War, a film by Harun Farocki, to whom we pay tribute. The excerpts operate as reflections that traverse filmic visuality. However, it is not about revealing images through words, but about excavating some layers of meaning through writing. Thus, this text, in a fragmented way, in dialogue with the German filmmaker's own methodological strategy, does not reveal, but rather proposes to unveil, like a set of playing cards laid out on the table, some images that reverberate in the present.